Menu

1. sendo p(x) = 5x²-2x + 1, calcule: a) p(1)b)p(2)c)p(-1)d)p(-2)e)p(3)

1. sendo p(x) = 5x²-2x + 1, calcule:
a) p(1)

b)p(2)

c)p(-1)

d)p(-2)

e)p(3)

1 Resposta
0

Só substituir os valores em cada letra, pelo x.

a) P(1) = 5x² - 2x + 1
Considerando x = 1:
P(1) = 5.1² - 2.1 + 1
P(1) = 5 - 2 + 1
P(1) = 4

b) P(2) = 5x² - 2x + 1
Considerando x = 2:
P(2) = 5.2² - 2.2 + 1
P(2) = 5.4 - 4 + 1
P(2) = 20 - 4 + 1
P(2) = 17

c) P(-1) = 5x² - 2x + 1
Considerando x = -1:
P(-1) = 5.-1² - 2.-1 + 1
P(-1) = 5.1 + 2 + 1
P(-1) = 5 + 2 + 1
P(-1) = 8

d) P(-2) = 5x² - 2x + 1
Considerando x = -2
P(-2) = 5.-2² - 2.-2 + 1
P(-2) = 5.4 + 4 + 1
P(-2) = 20 + 5
P(-2) = 25

e) P(3) = 5x² - 2x + 1
Considerando x = 3:
P(3) = 5.3² - 2.3 + 1
P(3) = 5.9 - 6 + 1
P(3) = 45 - 5
P(3) = 40